Mild and Efficient Oxidation ofPrimary and Secondary Alcohols Using NiO2/Silica Gel System (Solvent Free) - Mohammad Kooti; Soodabeh Amirian (E-Journal of Chemistry)
Oxidation of alcohols by nickel peroxide and silica gel system using grinding method has been studied. In the oxidation process, NiO2 is converted to NiO, which is recoverable.